Efficiency and imperfections of tilling machinery rental markets in the Brahmaputra Valley of eastern India - Anup Kumar Das; M P Bezbaruah (Agricultural Economics Research Review, 2023)
In rural India, farm capital goods rental markets enable small and marginal farmers to mechanize their operations. Imperfections can arise in these important factor markets because most suppliers are user-suppliers and only a few pure suppliers. User-suppliers hire out capital goods only after they have tilled their farms, and hiring-in users may not have access at the most opportune times. The market power of suppliers does not significantly impact or distort the markets by controlling the rental rates. Farming outcomes were better for owner-users than hiring-in users on average; the difference was statistically insignificant, however.